2004
DOI: 10.1001/archotol.130.3.324
|View full text |Cite
|
Sign up to set email alerts
|

Time Course in the Relief of Nasal Blockage After Septal and Turbinate Surgery

Abstract: To evaluate prospectively the time course of the change in efficacy of septal and turbinate surgery in relieving nasal obstruction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 19 publications
2
35
0
Order By: Relevance
“…Surgical correlation of septal deviations has been one of the most common procedures in otolaryngology, but, the objective evidence to support the efficacy of surgery is controversial. Although septoplasty and turbinectomy were two of the most commonly performed surgical procedures for relieving NAO (Manoukian et al, 1997), the long-term outcomes of such treatments are still not satisfactory (Jesson et al, 1989;Ho et al, 2004). Without any standard criteria, the decision to perform septoplasty was usually based on clinical observations alone (Konstantinidis et al, 2005;Singh et al, 2006).…”
Section: Models Of Nasal Airflow In Septal Deviation Pathologiesmentioning
confidence: 99%
“…Surgical correlation of septal deviations has been one of the most common procedures in otolaryngology, but, the objective evidence to support the efficacy of surgery is controversial. Although septoplasty and turbinectomy were two of the most commonly performed surgical procedures for relieving NAO (Manoukian et al, 1997), the long-term outcomes of such treatments are still not satisfactory (Jesson et al, 1989;Ho et al, 2004). Without any standard criteria, the decision to perform septoplasty was usually based on clinical observations alone (Konstantinidis et al, 2005;Singh et al, 2006).…”
Section: Models Of Nasal Airflow In Septal Deviation Pathologiesmentioning
confidence: 99%
“…The overall improvement of SNOT score after septoplasty was 71.13% which is comparable with many of the studies. Mean overall NOSE scale improvement was 65.88% done by Stewart et al 7 Total NOSE score benefit of 70% after septoplasty was observed by Rhee et al 8 Probability of 50% reduction of nasal obstruction was 73% after 3 months according to Ho et al 9 The figure of 77 % improvement in nasal obstruction compares favourably with other studies such as 80% by Denholm et al 10 14 Significant improvement of total nasal score in obstruction, sore throat & smell, but not much in headache was seen by Kantadinitis et al 15 In our study, improvement in other symptoms like, runny nose was 55%, sneezing 45%, facial pain 76%, cough 78%, epistaxis 80% and loss of smell 78%. These symptomatic improvements were comparable with other studies, but better than many of them.…”
Section: Discussionmentioning
confidence: 93%
“…The turbinate procedures include subtotal or total turbinectomy, mucosal cautery, submucous resection, and turbinate fracture. [12][13][14][15][16][17][18][19] In a large series, Rohrich et al 12 advocate submucous resection as an important adjunct to rhinoplasty. Mabry 13 popularized a partial turbinectomy technique, but recommended that the surgeon perform the most conservative surgical approach to the turbinates that consistently provides a good airway in that surgeon's hands.…”
Section: Discussionmentioning
confidence: 99%
“…Ho et al observed early improvements in nasal obstruction with septoplasty and turbinectomy but diminished Volume 120, Number 3 • Closed Septoturbinotomy benefit over time. 16 Some data support lateral outfracture in combination with submucous decongestion as the most effective approach to the hypertrophied turbinate while acknowledging the greater technical requirements for proper execution. 17 However, outfracturing the turbinates without resection has been even more controversial than actual excision of the turbinates.…”
Section: Discussionmentioning
confidence: 99%